Aku Cinta Lovina: Peran Sastra dalam Mempromosikan Pariwisata Bali Utara - Artawan, Gde (Jurnal Master Pariwisata (JUMPA); Volume 07, Nomor 01, Juli 2020, 2020)
The development of tourism in North Bali is indebted to literary writers and works, but their contributions are rarely realized. Lovina Beach which was the center of the growth of North Bali tourism was originally introduced in the 1970s by writer Panji Tisna, later by Sunaryono Basuki who wrote several stories set in Lovina. This article analyzes the novel Aku Cinta Lovina (I Love Lovina, 2017) by Sunaryono Basuki to show aspects of the story that promote North Bali tourism. The novel is examined with a literary approach to tourism, with a focus on how the novel portrays the tourist attraction of Lovina and the relationship between the host and guest. The results of the analysis show that the novel Aku Cinta Lovina shows the strong reciprocal relationship between literature and tourism, where writers promote tourism, at the same time writers get inspiration from tourism. Besides being intense in promoting North Bali tourism, this novel also portrays a harmonious relationship of host and guest that reinforces Balinese hospitality which is an important attraction of Bali tourism. Keywords: North Bali, host and guest, Lovina, literary tourism, hospitality